Effectiveness of Health Promotion by Indonesian Breastfeeding Association in Increasing Exclusive Breastfeeding Coverage in Surabaya City, East Java - Diani Octaviyanti Handajani; Eti Poncorini Pamungkasari; Uki Retno Budihastuti (Journal of Health Promotion and Behavior, 2018)
Background: Breastfeeding is essential for health, development, and child survival by preventing child illness. However, exclusive breastfeeding has not reached the desired target. Health promotion by Indonesian Breastfeeding Association (AIMI) participation is one way to increase exclusive breastfeeding coverage. There are several causative factors that influence exclusive breastfeeding, which can be explained by the PRECEDE-PROCEED model. This study aimed to determine the effectiveness of health promotion through the Association of Indonesian Breastfeeding Mothers (AIMI) in increasing coverage of exclusive breastfeeding in Surabaya, East Java.Subjects and Method: This was an analytic observational study with a cohort retrospective design. The study was conducted at AIMI Surabaya branch office and 6 community health centers in Surabaya, East Java, from December 2017 and January 2018. A total sample of 120 lactating mothers was selected for this study by simple random sampling. The dependent variable was breastfeeding. The independent variables were AIMI participation, maternal knowledge, maternal education, maternal attitude, family support, and peer support. The data were collected by questionnaire and analyzed by path analysis.Results: Exclusive breastfeeding increased with AIMI participation (b= 1.02; 95% CI= -0.19 to 2.24; p=0.101), better maternal knowledge (b= 1.48; 95% CI= 0.15 to 2.79; p=0.029), positive maternal attitude (b= 2.22; 95% CI= 1.03 to 3.38; p<0.001), and stronger family support (b= 2.69; 95% CI= 1.25 to 4.11; p<0.001). Maternal attitude increased with AIMI participation (b= 0.69; 95% CI= -0.18 to 1.57; p=0.116), better maternal knowledge (b= 1.56; 95% CI= 0.72 to 2.39; p<0.001), and higher maternal education (b= 0.71; 95% CI= -0.11 to 1.52; p=0.089). AIMI participation increased with higher education (b= 1.07; 95% CI= 0.26 to 1.87; p=0.009). Family support increased with stronger peer support (b= 2.24; 95% CI= 0.73 to 3.75; p=0.004).Conclusion: Exclusive breastfeeding increases with AIMI participation, better maternal knowledge, positive maternal attitude, and stronger family support.Keywords: exclusive breastfeeding, PRECEDE-PROCEED model, Indonesian Breastfeeding Association (AIMI)Correspondence: Diani Octaviyanti Handajani. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java. Email: diani.octaviyanti@gmail.com. Mobile: +628563328666Journal of Health Promotion and Behavior (2018), 3(1): 1-15https://doi.org/10.26911/thejhpb.2018.03.01.01